2017
DOI: 10.1111/1753-6405.12705
|View full text |Cite
|
Sign up to set email alerts
|

Regional survey supports national initiative for ‘water‐only’ schools in New Zealand

Abstract: Objective: To support a national initiative to remove sugary drinks from schools and limit drinks to water or unflavoured milk ('water-only'). Methods:We emailed all 201 schools with primary school aged children in the Greater Wellington region with a survey on (1) current status of, (2) support needs for, and (3) barriers to or lessons learned from, a 'water-only' school policy. Results:Only 78 (39%) of schools responded. Most supported 'water-only': 22 (28%) had implemented a policy; 10 (13%) in process of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Among a sample of Wellington (New Zealand) primary schools, although many had been thinking about or were in the process of implementing an official or unofficial water-only policy to help to curb children's consumption of sugarsweetened beverages, only 28% had actually implemented a water-only policy (43) . Barriers to school food policy implementation identified in a recent meta-analysis included lack of support and training for school staff, lack of acceptance of healthy foods by the school community, unhealthy fundraising practices, lower level of priority, and costs to implement the policy if needing to provide healthier foods or install canteen facilities and drinking-water fountains (44) .…”
Section: Political Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Among a sample of Wellington (New Zealand) primary schools, although many had been thinking about or were in the process of implementing an official or unofficial water-only policy to help to curb children's consumption of sugarsweetened beverages, only 28% had actually implemented a water-only policy (43) . Barriers to school food policy implementation identified in a recent meta-analysis included lack of support and training for school staff, lack of acceptance of healthy foods by the school community, unhealthy fundraising practices, lower level of priority, and costs to implement the policy if needing to provide healthier foods or install canteen facilities and drinking-water fountains (44) .…”
Section: Political Environmentmentioning
confidence: 99%
“…Barriers to school food policy implementation identified in a recent meta-analysis included lack of support and training for school staff, lack of acceptance of healthy foods by the school community, unhealthy fundraising practices, lower level of priority, and costs to implement the policy if needing to provide healthier foods or install canteen facilities and drinking-water fountains (44) . Similarly, the lack of prioritisation and value by schools and parental resistance were significant barriers to school policy implementation in New Zealand (42,43) . Support from school staff members and concerns for children's health tended to contribute to a successful implementation of a healthy food and beverage policy (44) .…”
Section: Political Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey of NZ schools found that most students (73%) had sugary drinks available to purchase on their grounds. For example, 30% of Primary Schools, 50% of Intermediate Schools, and 100% of High Schools had flavoured milk and/or juice available for purchase 11-12 …”
mentioning
confidence: 99%
“…For example, 30% of Primary Schools, 50% of Intermediate Schools, and 100% of High Schools had flavoured milk and/or juice available for purchase. [11][12] Because of the loopholes outlined above and the danger that sugary drinks pose to children, several NZ schools have implemented 'water only' policies, which do not allow sugary drinks to be sold by their canteens. 13 However, as outlined above, many schools have not implemented the simple 'water only' policy and therefore, the vast majority of NZ's children are still exposed to a product with devastating long-term consequences for them and for wider society (e.g.…”
mentioning
confidence: 99%